Konsep Pendidikan Karakter Anak Perspektif Imam Al-Ghazali dalam Kitab Ayyuha Al-Walad dan Relevansinya Ditengah Modernisasi Pendidikan - Saputra, Doni (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2023)
This study aims to describe and analyze the values ​​of children's character education in the book Ayyuha Al-Walad by Imam Al-Ghazali which is presented in advice, as well as describe and analyze its relevance in the midst of modernization of education. There are many problems regarding the moral degradation or character of children today, one of which is caused by technological developments that are difficult to compete with. Based on the explanation above, the writer formulates the problem 1) the concept of character education from Imam Al-Ghazali's perspective in the book of Ayyuha Al-Walad 2) the relevance of character education from the perspective of Imam Al-Ghazali in the book of Ayyuha Al-Walad amid the modernization of education. The data presented is sourced from the book Ayyuha Al-Walad . In addition, it is also supported by the work of Imam Al-Ghazali regarding the character of children.